2010
DOI: 10.1111/j.1751-1097.2010.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Photodynamic Therapy Using Water‐dispersed TiO2–Polyethylene Glycol Compound: Evaluation of Antitumor Effect on Glioma Cells and Spheroids In Vitro

Abstract: Titanium dioxide (TiO(2)) is thought to be a photocatalytic agent excited by UV light. Our aim was to investigate the photocatalytic antitumor effect of water-dispersed TiO(2) nanoparticles on C6 rat glioma cells and to evaluate the treatment responses by the spheroid models. Water-dispersed TiO(2) nanoparticles were constructed by the adsorption of chemical modified polyethylene glycol (PEG) on the TiO(2) surface (TiO(2)/PEG). Each monolayer and spheroid of C6 cells was coincubated with various concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 39 publications
1
67
0
2
Order By: Relevance
“…Hydrophilicity can be an important property of cell permeability of sensitizers [13], and TiO 2 /PEG nanoparticles have colloidal stabilization and dispersibility in aqueous solution. Our previous investigations have shown that these nanoparticles might attach to tumor cell membranes and be incorporated in tumor cells [32]. This experimental result indicated that the water dispersed TiO 2 /PEG exists in close vicinity of the cell membrane.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hydrophilicity can be an important property of cell permeability of sensitizers [13], and TiO 2 /PEG nanoparticles have colloidal stabilization and dispersibility in aqueous solution. Our previous investigations have shown that these nanoparticles might attach to tumor cell membranes and be incorporated in tumor cells [32]. This experimental result indicated that the water dispersed TiO 2 /PEG exists in close vicinity of the cell membrane.…”
Section: Discussionmentioning
confidence: 85%
“…We have developed a novel water-dispersed TiO 2 nanoparticle modified by polyethylene glycole (PEG) and demonstrated its photocatalytic anti-tumor effect on a glioma cell line [32]. These nanoparticle compounds are approximately 50 nm in diameter, and their dispersion and stability in an aqueous medium have been confirmed.…”
Section: Introductionmentioning
confidence: 97%
“…187,188 To date, light activation of TiO 2 NPs represents a major safety concern for nanotoxicology rather than a therapeutic opportunity, 185 although some reports exist. [189][190][191] Equivalent to common photosensitizers, QDs have also been proposed as intrinsic PDT agents. [192][193][194] However, the QYs of the singlet oxygen of QDs are very low compared to the ones of common photosensitizers (ca.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…The amount of formazan produced is directly proportional to the amount of LDH in the culture medium, which in turn is directly proportional to the number of dead or damaged cells (Korzeniewski & Callewaert, 1983). The size of spheroids after drug treatment has also been used as a measure of cell viability (Fehlauer et al, 2007;Johannessen et al, 2009;Khaitan et al, 2009;Yamaguchi et al, 2010). Khaitan et al (Khaitan et al, 2009) investigated the effect of the glycolytic inhibitor 2-deoxy-D-glucose on spheroids derived from a human glioma cell line by measuring the size of the spheroids after drug exposure.…”
Section: Spheroids and Chemotherapymentioning
confidence: 99%